A comparison of pre‐operative nerve stimulator‐guided femoral nerve block and fascia iliaca compartment block in patients with a femoral neck fracture. (21st June 2013) - Newman, B.; McCarthy, L.; Thomas, P. W.; May, P.; Layzell, M.; Horn, K.
Summary We undertook a randomised, controlled trial to compare the analgesic efficacy and opioid sparing effect of nerve stimulator‐guided femoral nerve block with fascia iliaca compartment block in patients awaiting surgery for fractured neck of femur. Ten‐centimetre visual analogue pain scores were measured before and 2 h after the block and opioid consumption was recorded in the 12‐h period after the block. One hundred and ten patients were randomly assigned. Femoral nerve block provided superior pre‐operative analgesia for fractured neck of femur compared with fascia iliaca compartment block. The difference in the mean reduction of pain score after the block was 0.9 (95% CI 0–1.8); p = 0.047. Patients receiving a femoral nerve block required less morphine after the block than those receiving fascia iliaca compartment block (p = 0.041).